Small G Protein StRab5b positively regulates potato resistance to Phytophthora infestans - Tian, Zaimin; Zhang, Zhiwei; Kang, Liru; Li, Min; Zhang, Jian; Feng, Yan; Yin, Jiang; Gong, Xuechen; Zhao, Jun (Frontiers in Plant Science, 2023)
Rab proteins are the largest members of the small G protein family and are widely distributed in eukaryotes.It comprises of eight subfamilies and are responsible for regulating vesicle transport, plant growth and development, and biotic and abiotic stress responses. In this study, we examined the regulation mechanism of StRab5b proteins on induce potato resistance against late blight caused by Phytophthora infestans. Our results indicate that the amino acid sequence of StRab5b showed the highest and lowest homology with NtRab5b and StRab which cloned from tobacco and potato respectively. The expression of StRab5b varied among different potato tissues and varieties, and it was effectively induced by P. infestans inoculation. In tobacco, the transiently ectopica expression of StRab5b enhanced resistance to P. infestans, whereas, silencing of StRab5b homologous gene facilitated pathogen infection. Furthermore, stable expression of StRab5b in potato increased resistance to P. infestans concomitantly with the accumulation of H2O2, as well as increasing the activities of ROS scavenge enzymes. In addition, LOX gene transcripts were upregulated rapidly after inoculation with P. infestans, indicating the involvement of jasmonic acid (JA) signaling in the StRab5b-mediated potato defense response. Collectively, our results suggest that StRab5b positively regulated the potato resistance against late blight in potato via JA mediated signalling pathway.